RESEARCH TRENDS IN LOCAL WISDOM-BASED CHEMISTRY LEARNING MEDIA: A SYSTEMATIC LITERATURE REVIEW 2015-2025 - Nurhalimah Sitinjak; Suyanta (Universitas Negeri Surabaya, 2026)
Chemistry education is often considered difficult because many concepts are abstract. Therefore, local wisdom-based learning media are needed to make learning more contextual and relevant to students’ experiences. This study aimed to map research trends on the integration of local wisdom into chemistry learning media using a Systematic Literature Review. Articles were collected from Scopus and Google Scholar (2015-2025), limited to empirical studies. Of the 515 initially identified articles, 24 met the inclusion criteria and were analyzed. The findings show that studies were dominated by the development of modules and e-modules (25%), mainly for high school students (88%), with acid-base chemistry being the most frequently studied topic (29.17%). Research variables focused on media feasibility (70.83%), while affective aspects, chemistry literacy, immersive digital media, and broader regional representation of local wisdom remain limited. This study provides research trend mapping and directions for developing more innovative and contextual chemistry learning media.